PENGARUH MODEL PEMBELAJARAN BRAIN BASED LEARNING BERBANTUAN MEDIA AUDIO TERHADAP KETERAMPILAN MENYIMAK SISWA MI NW BAGIK PAYUNG - ishthifaiyati, nurul (al-Hikmah : Jurnal Studi Islam, 2020)
The research  aimed  to determine the differences between group of students listening skills that learned by the learning model Brain Based Learning  , assisted by the audio media and group of students who learned by conventional model in class IV Cluster II Suralaga District, Lombok Timur Regency in academic year 2017/2018. This research included quasi-experimental research. The design was used non-equivalent posttest only control group design. The population of the study was the whole class IV in Cluster II Suralaga District, and the sample was class IV SDN 6 Suralaga and class IV SDN 1 Suralaga. The mothod collection was used by test method. The collected data were analyzed of  t-test.The results of this study indicate that there were significant differences in listening skills among groups of students that learned by learning model Brain Based Learning  , assisted by audio media and a group of students who learned by conventional learning model with tarithmetic greater than ttable (tarithmetic>ttable).It is shown by the taccount (12,25) >ttable (2,021) and average of exsperimental group (14,25) higher than average of control group (8). This means learning model application Brain Based Learning  , assisted by audio media was influence on listening skills class V students in Cluster I Suralaga District, Lombok Timur Regecy in academic year 2017/2018.